A hierarchical approach to solve a production planning and scheduling problem in bulk cargo terminal. (July 2016) - Menezes, Gustavo Campos; Mateus, Geraldo Robson; Ravetti, Martín Gómez
Highlights: This work deals with the integration of scheduling and lot-sizing decisions in bulk cargo terminal. The model and methodology are very general and they can be easily applied to several other situations. All instances are based on real case. Using a two-phase hierarchical framework, we are able to obtain very small gaps for real instances. Abstract: The integration of planning and scheduling decisions is key to obtain an efficient and reliable production operation in a modern manufacturing and service company. In this work we propose a mathematical model for this integration, the model is defined considering logistic operations at bulk port, however is generic enough to be adapted to several situations. The integration takes place in a hierarchical scheme where the problems exchange data and they are solved through a commercial solver and heuristics. When scheduling is not feasible, capacity information is forwarded to production planning to adjust or indicate the use of new tasks. The model and algorithms are validated considering data from a real case. Computational results show the efficiency of the approach, producing strong bounds for large instances.